On a system of quasilinear parabolic functional differential equations - Jäger, Willi; Simon, László (Acta mathematica hungarica, 2006)
We consider initial boundary value problems for a system of second order quasilinear parabolic equations where also the main part contains functional dependence on the unknown function.